“DINO Vs. DINI” educational game to increase children's cognitive abilities—what are its level elements? - Suharsiwi Suharsiwi; Nadiya Itsnaini Rachmawati; Sabeeha Hamza Dehham; Rani Darmayanti (Delta-Phi: Jurnal Pendidikan Matematika, 2023)
Games designed for children have the potential to serve as educational tools, incorporating learning components that promote engagement and facilitate the child's cognitive and developmental progress, tailored to their specific age group. The significance of Early Childhood Cognitive Abilities is in their association with everyday tasks and functions. The promotion of cognitive development in individuals with AUD necessitates the provision of many opportunities for cognitive stimulation. Children must attain fundamental competencies commensurate with their chronological age in cognitive development. The objective of developing this educational game is to assist early childhood education (PAUD) teachers and parents in delivering instruction through imaginative and inventive simulations. This study employs the Research and Development (R&D) technique, utilizing a 4D model. The instructional game incorporates many level features that assess difficulty, accuracy, memory, and thinking abilities. This educational game encompasses four distinct learning modules tailored for early infant development. These modules include word completion exercises, counting activities, picture guessing tasks, color identification exercises, and competitive elements. The utilization of educational games is anticipated to facilitate the enhancement of children's cognitive capacities, thereby preparing them for the subsequent stages of their primary education.